The Bright and Dark Side of Gossip for Cooperation in Groups - Dores Cruz, Terence D.; Beersma, Bianca; Dijkstra, Maria T. M.; Bechtoldt, Myriam N. (Frontiers in Psychology, 2019)
Recent experimental studies seem to concur that gossip is good for groups by showing that gossip stems from prosocial motives to protect group members from non-cooperators. Thus, these studies emphasize the “bright” side of gossip. However, scattered studies point to detrimental outcomes of gossip for individuals and groups, arguing that a “dark” side of gossip exists. To understand the implications of gossip for cooperation in groups, both the dark and bright side of gossip must be illuminated. We investigated both sides of gossip in two scenario studies. In Study 1 (N = 108), we confronted participants with a free-rider in their group and manipulated whether the gossip recipient was the free rider’s potential victim or not. Participants showed a higher group protection motivation in response to gossip when imagining to gossip to a potential victim of a norm violator compared to a non-victim. They showed a higher emotion venting motivation when imagining to gossip to a non-victim compared to a potential victim. Both these gossip motives related to an increased tendency to gossip. In Study 2 (N = 104), we manipulated whether participants were the targets or observers of gossip and whether the gossip was true or false. Results showed that targets of negative gossip intended to increase their work effort in the short run, but only when the gossip was true. Furthermore, gossip targets reported lower long-term cooperative intentions towards their workgroup regardless of gossip veracity. This paper demonstrates that gossip has both a “dark” and “bright” side and that situational factors and agent perspectives determine which side prevails.